A computational mechanistic study of the cleavage of sulfur-sulfur bond by Frustrated Lewis Pairs. (12th April 2023) - Qin, Lei; Zhang, Zhaoyin; Liu, Ruiqin; Zhou, Ming; Zhao, Lili
Graphical abstract: DFT calculations were performed to gain insight in to the mechanism of SS bond cleavage in disulfides mediated by Frustrated Lewis Pairs. Abstract: DFT calculations were performed to gain insight into the detailed mechanism of SS bond cleavage in disulfides (i.e., i PrSS i Pr) by a frustrated Lewis pair (FLP) ( t Bu)3 P/B(C6 F5 )3 . The calculations revealed that the reaction initiates from the generation of weak complex B(C6 F5 )3 / i PrSS i Pr (IM1 ) between i PrSS i Pr and Lewis acid B(C6 F5 )3 . Subsequently, the Lewis base ( t Bu)3 P can activates the SS bond leading to the final cleavage of SS bond to give the product [( t Bu)3 P(S i Pr)][( i PrS)B(C6 F5 )3 ] (PR ). The computed kinetics and thermodynamics suggest that the reaction can take place reversibly under ambient conditions, which accounts well for the experimental observations. Furthermore, the mechanism is compared with that of the HH bond cleavages by same FLP. Contrast to the HH bond cleavage, a weak donor–acceptor complex IM1 between i PrSS i Pr and B(C6 F5 )3 could be located before SS bond cleavage. Nonetheless, the complete SS bond cleavage essentially is still due to the synergistic catalytic Lewis acid/base effects of FLP ( t Bu)3 P/B(C6 F5 )3 .